Pengaruh Kemampuan Kerja dan Motivasi terhadap Kinerja Pegawai (Studi kasus pada BMT di wilayah Sepanjang Sidoarjo). - Faizah, Nur; Seno Aji, Toni (Jurnal Ekonomika dan Bisnis Islam, 2019)
Employee performance is an important thing because performance shows the results of every work performed by employees. Employee performance increases seen from employees able to meet the targets set by company. This research is a quantitative research that aims to determine whether the ability and motivation of work affect employee performance in BMT in Sepanjang, Sidoarjo Regency. The method in this reseach is associative which means there is a relationship or influence between variables one with other variables. The population used in the study amounted to 30 respondents from all employees at BMT in the Sepanjang Sidoarjo region using saturated sampling techniques. The results of this study indicate that partially, the variabke work ability does not effect employee performance and motivation influence the performance and motivation influence the performance of employees on BMT in Sepanjang Sidoarjo.